Effect of Hyaluronic Acid/Trehalose in Two Different Formulations on Signs and Symptoms in Patients with Moderate to Severe Dry Eye Disease - Klemens Fondi; Piotr A. Wozniak; Doreen Schmidl; Ahmed M. Bata; Katarzyna J. Witkowska; Alina Popa-Cherecheanu; Leopold Schmetterer; Gerhard Garhöfer (Journal of Ophthalmology)
Purpose. This randomized, observer-masked, crossover study investigated the effect of two hyaluronic acid/trehalose-based containing formulations, with different physical properties, on the signs and symptoms in patients with moderate to severe dry eye disease (DED). Methods. In one group, patients received a mixture of sodium hyaluronate and trehalose (HT, Thealoz Duo®) for use during the day. In the other group, patients received a more viscous formulation consisting of hyaluronic acid, trehalose, and carbomer (HTC-gel, Thealoz Duo Gel) to use pro re nata. Both groups used HTC-gel before going to bed. Clinical standard tests for DED were performed at the beginning and end of each one-week period. Further, patient satisfaction including quality of sleep was assessed using a visual analogue scale. Results. Corneal fluorescein and conjunctival lissamine green staining scores decreased, and tear breakup time (BUT) increased for both groups (p<0.001 each). Mean instillation frequency was 3.1 ± 2.6 drops/day when using HT and 1.9 ± 2.2 drops/day when using HTC-gel (p=0.02). A significant improvement in the quality of sleep was observed with both treatments (p=0.01). Conclusions. Our results show improvement in signs and symptoms of DED in both groups. While instillation of HTC-gel resulted in a lower instillation frequency, both formulations of trehalose showed good clinical efficacy. This trial is registered with NCT02980913.